Join process of splice graft in tomato (Solanum lycopersicum L.) - Velasco-Alvarado, Mario de J.; Castro-Brindis, Rogelio; Avitia-García Edilberto; Castillo-Gonzáles Ana María; Sahagún- Castellanos Jaime; Lobato-Ortiz, Ricardo (Revista Mexicana de Ciencias Agrícolas, 2017)
The tomato grafting technique represents a sustainable alternative for disease control, increasing plant vigor, improving fruit quality and yield. The first important factors in the grafting process are the anatomical compatibility and the time of establishment of vascular continuity between the two plant tissues, the latter determining the moment of transplantation. The objective of this paper was to evaluate the process of graft joining with the splicing method in tomato, by means of anatomical cuts in the attachment point; as well as to determine the time of planting time between the ‘Multifort’ and ‘El Cid’ genotypes (rootstock and graft, respectively) to synchronize the stem diameter. 100 seeds of both genotypes were sown, from these seedlings the stem diameters were measured daily. Tissue samples were taken from the graft attachment site at 5, 10 and 15 days after grafting (DDI), anatomical sections were 10 μm thick obtained with a rotary microtome. The results indicated that it is necessary to plant the graft or spike two days before the rootstock to in order to homogenize the stem diameter to 2 mm (ideal for grafting). In the images of the anatomical sections it was found that at 5 DDI the demarcation line began to be reabsorbed and at the same time the formation of new conduction tissue (xylem and phloem) began, the complete vascular connection was carried out at the 10 DDI.